Near-infrared lipophilic fluorophores for tracing tissue growth - Kim, Soon Hee (2013)
Longitudinal monitoring of cell migration, division and differentiation is of paramount importance in cell-based medical treatment. However, currently available optical techniques for tracing cell growth and tissue development are limited in applications due to genetic modification, toxicity and inaccurate detection when utilizing the visible spectrum. We have developed lipophilic near-infrared (NIR) fluorophores with high optical properties and a low background signal that allows longitudinal monitoring of cell proliferation and differentiation. Intracellular labeling efficacy was highly dependent on the physicochemical properties of fluorophores such as lipophilicity, charge, polar surface area and rotational bonds. Among the series of NIR cyanine fluorophores, ESNF 13 showed high solubility in aqueous buffer, high membrane penetration, low cytotoxicity and a long-term signal maintainability with a high signal intensity. This study will guide tissue engineers in designing long-term cell trafficking agents with better physicochemical and optical properties.